Perancangan Sistem Informasi Administrasi Keuangan pada Kampus Akbid Sentra Bina Yudhistira Tangerang - Mulkan Syarif; Setiaji Setiaji (Syntax Literate, 2022)
Akbid Sentra Bina Yudistira (SBY) located in Tangerang is one of the educational institutions that still uses a manual system in processing administrative data. The data is recorded manually in a book and then processed using Microsoft Excel. The condition of the financial system that is currently running at Akbid Sentra Bina Yudistira (SBY) makes it difficult for the administrative staff of the finance department to process administrative data. The author uses the waterfall software development method to make this application. By implementing a web-based information system, it can provide efficiency and the administrative system can run effectively. Training is required for the Admin before this system can be implemented so that the content in the website application can run according to its function.